2011
DOI: 10.1073/pnas.1007694108
|View full text |Cite
|
Sign up to set email alerts
|

AMP kinase-related kinase NUAK2 affects tumor growth, migration, and clinical outcome of human melanoma

Abstract: The identification of genes that participate in melanomagenesis should suggest strategies for developing therapeutic modalities. We used a public array comparative genomic hybridization (CGH) database and real-time quantitative PCR (qPCR) analyses to identify the AMP kinase (AMPK)-related kinase NUAK2 as a candidate gene for melanomagenesis, and we analyzed its functions in melanoma cells. Our analyses had identified a locus at 1q32 where genomic gain is strongly associated with tumor thickness, and we used re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…Strikingly, the exact same GO terms were enriched for miR-143, GO:0042981 'regulation of apoptosis' (Benjamini-Hochberg P = 0.049), GO:0043067 'regulation of programmed cell death' (BenjaminiHochberg P = 0.033) and GO:0010941 'regulation of cell death' (Benjamini-Hochberg P = 0.025). Target genes encompassed by these GO terms for both miRNAs included those normally upregulated in oncogenesis, such as NUAK2 (Namiki et al 2011), EGFR (copy number gain seen in 4% SBNETs (Banck et al 2013)), KRAS, NRAS, IGF1 , Reidy-Lagunes et al 2012, MAPK1 (ERK1) , BCL2, ARHGEF7 and BMP7 (Supplementary Table 4). Target genes specific only for miR-1 included HGF (Svejda et al 2013) and VEGFA.…”
Section: :9 Micrornas Appear Deregulated In Liver Metastases From Smentioning
confidence: 99%
“…Strikingly, the exact same GO terms were enriched for miR-143, GO:0042981 'regulation of apoptosis' (Benjamini-Hochberg P = 0.049), GO:0043067 'regulation of programmed cell death' (BenjaminiHochberg P = 0.033) and GO:0010941 'regulation of cell death' (Benjamini-Hochberg P = 0.025). Target genes encompassed by these GO terms for both miRNAs included those normally upregulated in oncogenesis, such as NUAK2 (Namiki et al 2011), EGFR (copy number gain seen in 4% SBNETs (Banck et al 2013)), KRAS, NRAS, IGF1 , Reidy-Lagunes et al 2012, MAPK1 (ERK1) , BCL2, ARHGEF7 and BMP7 (Supplementary Table 4). Target genes specific only for miR-1 included HGF (Svejda et al 2013) and VEGFA.…”
Section: :9 Micrornas Appear Deregulated In Liver Metastases From Smentioning
confidence: 99%
“…Moreover, the incidence of both adenomas and aberrant crypt foci were significantly higher in SNARK(+/-) mice than in their wild-type counterparts, suggesting that SNARK deficiency contributed to the early phase of tumourigenesis via obesity-dependent and obesity-independent mechanisms [14]. Recently, Namiki et al [14] have shown that AMP kinase-related kinase SNARK affects tumour growth, migration, and clinical outcome of human melanoma, further supporting the importance of this protein kinase in cancer development and tumour progression, while AMPK has antioncogenic properties. We have also shown that the SNF1/AMP-activated protein kinase-related kinase is a sensitive marker for the action of ecotoxicant methyl tert-butyl ether (MTBE) as well as silver nanoparticles [15,16].…”
Section: Introductionmentioning
confidence: 95%
“…This activity is believed to be due to their activation by various forms of metabolic stress such as glucose deprivation, a condition to be expected within solid tumours [28]. Recently, Namiki et al [14] showed that AMP kinase-related kinase NUAK2 affects tumour growth, migration, and clinical outcome of human melanoma. This study further supports the importance of NUAK2 in cancer development and tumour progression, while AMPK has antioncogenic properties.…”
Section: Protein Kinase Snark and Tumourigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…1). In terms of human disease, NUAK2 was shown to contribute to the development of melanomas (Namiki et al, 2011). Other roles for NUAK2 were identified in heterozygous NUAK2 mice, which display mature-onset obesity and related metabolic disorders and also have a higher risk of developing colorectal cancers.…”
mentioning
confidence: 99%